PROPOSED SOLUTION TO OPTIMIZE PEOPLE RESOURCING STRATEGY AT PT CHINA COMSERVICE INDONESIA WEST JAVA REGION) - Rona Maya Salfina; Anggara Wisesa (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
China Communications Services Corporation Limited (CCS) is a leading service provider providing integrated support services in the information sector, including telecommunications, media, and technology. PT China Comservice Indonesia Regional West Java primarily has contract employees because the company runs its business activities based on projects at consumers' request. This research aims to provide solutions to companies regarding existing problems. The research method used in this research is a qualitative method with an ethnographic approach by understanding and describing an event that occurs in an organization. Based on the issue obtained by researchers at the company, companies often experience a shortage of human resources when there are new projects, causing a lack of effectiveness and efficiency in implementing subsequent projects. The researcher analyzes the company's data and the situation regarding human resource strategy related to human resource planning, recruitment and selection, talent management, and retention planning to find the root cause of the issue. From these issues, the researcher recommends the company create a program for talent management and retain planning for employees in the company, aiming to get employees who are competent and loyal to the company. These programs can help companies improve the company and their employees' performance.